Recent Advances in Herbal Medicines – An Updated Review - Roy, Dhritiman; Chakraborty, Arindam; Mukherjee, Payel; Ghosh, Balaram; Chakraborty, Manas (Asian Journal of Pharmaceutical Research and Development, 2022)
Nowadays peoples throughout the world have been attracting towards the herbal medicines. Worldwide favour the traditional healthcare system, so day-by-day uses of herbal remedies to cure diseases is increase instead of alternative medicines. Herbal drugs have an ability to maintain health and to treat various diseases therefore herbal drugs have been used since very earlier days. To fulfil the public requirement many companies have been using herbal drug technology for converting botanical materials into medicines, where standardization, quality control, modern scientific techniques and traditional knowledge are very necessary. This review focuses on recent trends in Herbal drugs and main motto is to explain the therapeutic effectiveness of various herbal drugs, adverse drug reactions, drug interactions, standardization and stability testing of herbal medicines, pharmacovigilance and regulatory status of herbal medicines.